Pendidikan Kecakapan Hidup di Pondok Pesantren - Iyoh Mastiyah (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
Education on life skills is the abilities which learner needs to face his social, economics, politics, and religious life so that he can reach happiness and welfare in this world and hereafter. One of the Islamic institution that deal with these goals above is pesantren. One of method which is used in teaching and learning process in pesantren is sorogan that can be used to applicate education on life skills. Education on life skills is held dealing with the purpose that santri should be given the knowledge to face the global change. This short article concerns on educational life skills in pesantren through sorogan method.